A silicon-ammonia quantum dot, Ti3C2Mxene@Si-QDs composite material, photodetector and its preparation method

CN122742477BActive Publication Date: 2026-11-03甘肃省科学院 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611150618.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-11-03
Estimated Expiration
2046-07-31

AI Technical Summary

Technical Problem

Traditional silicon-based photodetectors have low responsivity and slow response speed, especially in the deep ultraviolet or specific wavelength bands where the optical signal conversion efficiency is limited.

Method used

A photodetector was fabricated by using aminated silicon quantum dots and layered Ti3C2MXene composite material, and by constructing nanopillar arrays and interfacial heterojunctions on the silicon-based surface, combined with optical field modulation and carrier separation and transport mechanisms.

Benefits of technology

It significantly enhances light absorption efficiency, improves responsivity and response speed, broadens the light response range, and achieves high-sensitivity photoelectric detection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122742477B_ABST
    Figure CN122742477B_ABST
Patent Text Reader

Abstract

The application discloses an amino-silicon quantum dot, a Ti3C2 Mxene@Si-QDs composite material, a photoelectric detector and a preparation method thereof, and the preparation method comprises the following steps: preparing a Si quantum dot (Si-QDs) modified Ti3C2 MXene composite material; preparing a prismatic super surface structure on the surface of a silicon substrate; combining the composite material on the super surface structure to form a photoelectric conversion area; and finally preparing an electrode. According to the application, the light trapping effect of the silicon super surface is used to enhance light absorption, the quantum confinement effect of the Si-QDs is used to improve the photo-generated carrier generation efficiency, and the high mobility characteristic of the layered Ti3C2 MXene is used to realize the rapid transport and collection of the carriers. The three work together to significantly improve the responsivity and response speed of the photoelectric detector, and the problem of insufficient performance of a traditional silicon-based detector is overcome, so that the application has a wide application prospect in the fields of optical communication and sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photodetector materials and device fabrication technology, and more specifically, to an aminated silicon quantum dot, a Ti3C2Mxene@Si-QDs composite material, a photodetector, and a method for fabricating the same. Background Technology

[0002] Photodetectors, as devices that convert optical signals into electrical signals, have wide applications in fields such as fiber optic communication, image sensing, environmental monitoring, and biomedicine. With technological advancements, increasingly higher demands are being placed on the responsivity, response speed, and detection sensitivity of photodetectors.

[0003] While traditional silicon-based photodetectors have mature manufacturing processes, their responsivity and quantum efficiency are often limited due to silicon's indirect bandgap and limited light absorption coefficient. Especially in the deep ultraviolet or specific wavelength ranges, silicon has a small light penetration depth, and surface defects easily lead to carrier recombination, thereby reducing internal quantum efficiency.

[0004] In recent years, metasurface structures have attracted much attention due to their ability to manipulate light fields at subwavelength scales. By etching nanopillar arrays onto silicon wafers, localized enhancement and light-trapping effects of incident light can be achieved, effectively increasing the interaction length between light and materials. For example, existing technologies employ photolithography to fabricate nanopillar arrays on silicon substrates for superlenses or Raman enhancement. Meanwhile, two-dimensional MXenes, as novel two-dimensional transition metal carbides / nitrides, possess excellent metallic conductivity and hydrophilic surfaces, showing great potential in optoelectronics. However, the light absorption capacity of pure MXene films is limited. Combining nanomaterials (such as silicon quantum dots (Si-QDs)) with two-dimensional MXenes can leverage the size effect of Si-QDs to enhance light absorption and achieve rapid carrier separation and transport through interface effects.

[0005] Currently, there is no technical solution that can organically combine the optical field modulation capability of silicon-based metasurfaces with the high-efficiency photoelectric conversion characteristics of Si-QDs-modified layered Ti3C2MXene materials to prepare high-performance photodetectors with both high responsivity and fast response speed. Summary of the Invention

[0006] The purpose of this invention is to provide an aminated silicon quantum dot, a Ti3C2Mxene@Si-QDs composite material, a photodetector, and a method for preparing the same, so as to overcome the problems of low responsivity or slow response speed of silicon-based detectors in the prior art.

[0007] To achieve the above-mentioned objectives, the present invention employs the following technical solution: A method for preparing aminated silicon quantum dots involves completely dissolving DAPH in deionized water at a concentration of 2-4 mg / ml under stirring at room temperature; then adding DAMO (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane) dropwise at a volume ratio of (0.1-1):1 to deionized water; continuing the reaction under stirring at room temperature; after the reaction is complete, filtering the solution using a membrane with a pore size of 0.1 μm-0.22 μm, and then dialyzing the solution in deionized water using a dialysis bag with a molecular weight cutoff of 500 Da-3000 Da to obtain a purified aminated silicon quantum dot (Si-QDs) solution.

[0008] A layered Ti3C2MXene@Si-QDs composite material includes the aforementioned aminated Si-QDs. The composite material comprises multilayer Ti3C2MXene material and Si-QDs loaded on the surface and / or between the layers of the multilayer Ti3C2MXene material. The surface of the Si-QDs contains amino functional groups. The Si-QDs are tightly anchored to the Ti-O-Si bonds through hydrogen bonding and / or chemical bonding between the amino functional groups and the oxygen-containing groups -O, -OH and / or fluorine-containing groups -F at the ends of the surface of the multilayer Ti3C2MXene material, forming a stable interfacial contact.

[0009] Furthermore, the multilayer Ti3C2MXene has an accordion-like layered structure.

[0010] Furthermore, the particle size of the Si-QDs is 2 to 10 nm, and the particle size distribution deviation does not exceed ±1.5 nm; the mass ratio of the Si-QDs to the multilayer Ti3C2MXene material is 1:(1 to 10).

[0011] A method for preparing the above-mentioned layered Ti3C2MXene@Si-QDs composite material includes the following steps: (1) Preparation of layered Ti3C2MXene material: The ground and sieved Ti3C2Al MAX phase powder was slowly added to a hydrofluoric acid solution with a mass fraction of 30%~50% under stirring conditions, and reacted at 20°C~30°C for 12 h~48 h; after the reaction, the supernatant was discarded by centrifugation, and the black precipitate was repeatedly washed with ultrapure water until the pH of the washing solution was 6.5~7.0. Finally, it was vacuum dried at 40°C~60°C to obtain accordion-shaped multilayer Ti3C2 MXene material; (2) Preparation of Si-QDs dispersion; (3) The multilayer Ti3C2MXene material obtained in step (1) is ultrasonically dispersed in an ethanol / water mixed solvent; under stirring conditions, the aminated Si-QDs solution obtained in step (2) is added dropwise to the above dispersion; the reaction is continued to be stirred at 20°C ~ 30°C for 12 h ~ 48 h; after the reaction is completed, the black precipitate is collected by centrifugation, washed repeatedly with an ethanol / water mixed solvent, and finally dried under vacuum at 40°C ~ 60°C to obtain the layered Ti3C2MXene@Si-QDs composite material.

[0012] A photodetector based on metasurface structure and MXene material comprises the aforementioned multilayer Ti3C2MXene@Si-QDs composite material. The photoelectric conversion region of the photodetector is composed of a silicon-based metasurface structure and a layered Ti3C2MXene@Si-QDs composite material. The metasurface structure is a nano-frustum array formed by Si-based semiconductor material, and the multilayer Ti3C2MXene@Si-QDs composite material covers the surface of the silicon-based metasurface structure.

[0013] Furthermore, the spacing between adjacent frustum subunits of the metasurface structure is 500 nm-1 μm.

[0014] A method for fabricating the above-mentioned photodetector based on metasurface structure and MXene composite material, the method comprising the following steps: Step 1: Provide a heavily doped silicon substrate; Step 2: Define the planar pattern of the silicon metasurface structure on the surface of the silicon substrate using a photolithography process; Step 3: Based on the surface pattern, a three-dimensional silicon metasurface structure is formed on the silicon substrate surface using deep reactive ion beam and dynamic rotating ion beam etching processes; Step 4: Prepare layered Ti3C2 MXene@Si-QDs composite material; Step 5: The layered Ti3C2 MXene@Si-QDs composite material is bonded to the surface of the silicon-based metasurface structure to form a photoelectric conversion composite layer; Step 6: Prepare a transparent signal acquisition anode electrode on the photoelectric conversion composite layer, and prepare a metal thin film signal acquisition cathode electrode on both sides of the photoelectric conversion composite layer to obtain a photodetector.

[0015] Furthermore, the silicon metasurface structure formed in step 3 is first formed into pillars with a diameter of 500nm-1μm and a height of 100nm-1μm by deep reactive ion beam etching (DRIE) process; then, the sidewalls of the pillar structure are etched at different rates by multi-stage large-angle dynamic rotating ion beam etching (Angled-IBE) technology to form frustum-shaped microstructure units.

[0016] Furthermore, the anode electrode prepared in step 6 is a transparent mesh structure Ag nanowire, which is reliably overlapped with the metal thin film on both sides of the light absorption composite layer; the cathode electrode for signal acquisition is a ring structure or strip structure metal thin film outside the anode overlap area.

[0017] The technical principle of this invention is as follows: 1. Improved construction logic of heterojunction interfaces This approach utilizes the chemical affinity between the abundant amino functional groups on the surface of silicon quantum dots (Si-QDs) and the oxygen- and fluorine-containing terminals (–O, –OH, –F) on the surface of multilayer Ti3C2 MXene to drive self-assembly. The Si-QDs are prepared using DAPH and DAMO, and their surfaces contain a large number of amino groups (–NH2); while the HF-etched Ti3C2 MXene surface is rich in polar functional groups such as –O, –OH, and –F. A tight and uniform interfacial bond can be achieved between the two through hydrogen bonding or electrostatic interactions, forming a stable 0D / 2D heterostructure.

[0018] 2. Improvement of the synergistic mechanism between carrier separation and transport In this scheme, silicon quantum dots (SQDs) and multilayer Ti3C2 MXene materials form a tight 0D / 2D heterojunction. Photogenerated carriers can be efficiently separated and transported at the interface between Si-QDs and MXene materials. After the Si-QDs absorb photons and generate electron-hole pairs, electrons can be rapidly injected into the highly conductive Ti3C2 MXene layer, while holes remain in the Si-QDs, effectively suppressing carrier recombination. Simultaneously, the accordion-like layered structure of the multilayer MXene material provides a continuous carrier pathway, which is beneficial for the rapid collection and transport of photogenerated carriers.

[0019] The role of the metasurface structure combined with the Ti3C2MXene@Si-QDs composite material in this invention: 1. Improvement of photoelectric detection performance Expanding the optical response range: Silicon quantum dots have size-tunable band gaps, which can compensate for the insufficient absorption of Ti3C2MXene materials in specific wavelength bands; Enhanced light absorption: Uniform dispersion of Si-QDs on the surface of Ti3C2MXene material can increase the effective light absorption area; Accelerating carrier separation: The built-in electric field formed at the 0D / 2D heterojunction interface can promote the effective separation of photogenerated electron-hole pairs; Reduce carrier recombination loss: Highly conductive multilayer Ti3C2MXene materials serve as fast electron transport channels, which can reduce carrier recombination.

[0020] 2. Effect on material stability While silicon quantum dots have advantages such as compatibility with microelectronic processes and good biocompatibility, they often face problems of surface oxidation and insufficient stability in device applications.

[0021] In this scheme, Si-QDs are tightly anchored to the surface / interlayer of Ti3C2MXene material through chemical interactions between surface amino groups and functional groups on the surface of Ti3C2MXene material. The layered structure of Ti3C2MXene material can physically encapsulate and protect Si-QDs, which helps to suppress the surface oxidation of silicon quantum dots and improve the environmental stability of the composite material.

[0022] 3. Impact on device fabrication process In existing technologies, the fabrication of MXene-quantum dot composite photodetectors often involves complex processes such as high-temperature treatment, vacuum equipment, or multi-step deposition.

[0023] In this scheme, the entire preparation process of Ti3C2 MXene@Si-QDs composite material is completed under ambient temperature, ambient pressure, and aqueous phase conditions. It does not require high-temperature annealing or vacuum equipment, and is highly compatible with solution processing technology, which is conducive to the preparation of low-cost, large-area photodetectors.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Significantly enhances light absorption efficiency, overcoming the intrinsic absorption limitations of silicon-based materials. A silicon-based metasurface structure is fabricated on the light incident surface of the device. Utilizing an array of nano-pyramidal structures, incident light can be localized within the subwavelength scale, improving light capture and re-radiation, and significantly increasing the absorption of light by silicon. By optimizing the geometric parameters of the metasurface micro / nanostructure, selective enhanced absorption can be achieved at specific wavelengths or bands. Simultaneously, the size-tunable bandgap characteristics of Si-QDs provide the composite material with additional degrees of freedom for light absorption control. The synergistic effect of the localized optical field enhancement effect of the metasurface and the quantum confinement effect of Si-QDs enables the device to maintain high responsivity and high specific detectivity in the visible to near-infrared range, effectively overcoming the technical bottleneck of traditional silicon-based detectors where the detection capability drops sharply in the near-infrared band (wavelength > 1100 nm) due to the intrinsic bandgap limitation of silicon.

[0025] 2. Constructing efficient carrier separation and transport channels to achieve ultra-high sensitivity detection. Compared with existing silicon-based photodetectors, on the one hand, a 0D / 2D heterojunction is formed between zero-dimensional Si-QDs and layered Ti3C2MXene composite materials. The difference in work function at the interface creates a strong built-in electric field, allowing photogenerated electrons to be rapidly injected into the highly conductive layered channels of Ti3C2MXene material for efficient transport. At the same time, Ti3C2MXene material, with its excellent metallic conductivity, provides a high-speed transport path for carriers. This integrated "generation-separation-transport" synergistic mechanism significantly suppresses the recombination of photogenerated carriers, significantly improves the responsivity and response speed of the photodetector, and overcomes the performance deficiencies of traditional silicon-based detectors. Attached Figure Description

[0026] Figure 1 This is a side view of the photodetector structure of the present invention; Figure 2 This is a schematic cross-sectional view of the photodetector of the present invention; Figure 3 This is a schematic diagram of photolithography and etching for a silicon-based metasurface structure according to an embodiment of the present invention. Figure 1 ; Figure 4 This is a schematic diagram of photolithography and etching for a silicon-based metasurface structure according to an embodiment of the present invention. Figure 2 ; Figure 5 This is a schematic diagram of the silicon-based metasurface structure of the photodetector according to an embodiment of the present invention; Figure 6 SEM and TEM images of Ti3AlC2MAX powder (the raw material used to prepare layered Ti3C2MXene), layered Ti3C2MXene, Si-QDs, and Si-QDs-modified layered Ti3C2MXene composites; Figure 7 Fourier transform infrared spectra of Si-QDs, and Fourier transform infrared spectra of Ti3C2MXene and Ti3C2MXene@Si-QDs materials; Figure 8 This is a SEM image of the mesh transparent anode formed by the embodiment of the present invention; Figure 9 This is a photolithographic schematic diagram of the cathode contact area in an embodiment of the present invention; Figure 10 This is a schematic diagram of cathode contact etching according to an embodiment of the present invention; Figure 11 This is a schematic diagram illustrating the preparation of the cathode contact and anode overlap in an embodiment of the present invention; Figure 12 The above are the light reflectance test results of photodetectors with different structures according to embodiments of the present invention; Figure 13The transient optical response of the photodetector in this embodiment of the invention is shown in the form of a 635nm laser (5mW) light source. Figure 14 The transient optical response of the photodetector in this embodiment of the invention is shown in the image at a 980nm laser (5mW) light source. Figure 15 This is a single-point scanning imaging effect of the photodetector in an embodiment of the present invention (635nm light source). In the diagram: B01 - n-type heavily doped conductive layer; B02 - p-type heavily doped conductive layer; C01 - cathode signal acquisition terminal; C02 - anode signal acquisition connector; A01 - light absorption unit; N01 - light-transmitting anode. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments.

[0028] This embodiment provides a photodetector based on metasurface structure and MXene material and its fabrication method.

[0029] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0030] Please refer to Figure 1 and Figure 2 , Figure 1 This is a side view of a photodetector based on a metasurface structure and MXene composite material. Figure 2 for Figure 1 A cross-sectional view along the radial direction D-D'. The detector structure consists of a single-crystal silicon substrate (not shown), an n-type heavily doped conductive layer B01 and a p-type heavily doped conductive layer B02 grown on the substrate, a cathode signal acquisition terminal C01, a light absorption unit A01, and a light-transmitting anode N01 fabricated on the top layer of A01, with the anode signal acquisition junction C02. The light absorption region A01 is composed of a frustum-shaped silicon-based metasurface structure and layered Ti3C2MXene@Si-QDs material.

[0031] In this embodiment, the silicon-based metasurface structure in the light absorption region A01 is composed of a frustum-shaped subunit array. The bottom of each subunit in the frustum-shaped microstructure array is formed by a columnar array with a diameter of 500 nm-1 μm, a nanopillar diameter of approximately 500 nm, and a period of approximately 500 nm, through staged rotating ion beam etching. Layered Ti3C2 MXene@Si-QDs composite material is distributed on the surface or in the gaps of the frustum-shaped microstructure. Figure 1The mid-layered Ti3C2MXene@Si-QDs composite material is not shown, and the mesh transparent cathode covers the top layer of the layered Ti3C2MXene@Si-QDs composite material.

[0032] Step 1: Substrate Preparation 6-inch single-sided polished monocrystalline silicon wafers (Si / Si) were selected. n- / Si P+ The silicon wafer was used as a substrate. It was placed in acetone, anhydrous ethanol and deionized water in sequence, and ultrasonically cleaned for 10 minutes each to remove organic contaminants and particles from the surface. Finally, it was dried with nitrogen gas.

[0033] Step 2: Photolithography to define the pattern See attached Figure 3 A UV positive photoresist (such as AZ 5214 or SPR220) is spin-coated onto the polished surface of a substrate using a spin-coating process at a speed of 3000~4000 rpm and a thickness of about 1~2 μm. The substrate is then pre-baked at 110°C for 90 s. A metasurface pattern is then projected onto the photoresist layer using a UV lithography machine (wavelength 365 nm, i-line) with an exposure dose of 100~200 mJ / cm². After exposure, the layer is post-baked at 110°C for 60 s, then developed with 2.38% TMAH developer for 40~60 s. Finally, the photoresist mask pattern is obtained after fixing with deionized water.

[0034] Step 3: Etching to form silicon metasurface structure See appendix Figure 4 Using the photoresist pattern obtained in step 2 as a mask, a silicon wafer was deeply etched using an inductively coupled reactive ion etching (ICP-DRIE) system. The sample was then transferred into an ICP-DRIE chamber for etching. The etching process involved introducing SF6 (100-200 sccm, ICP power 1500-2000 W, bias power 10-50 W) for 5-15 seconds, followed by a passivation process using C4F8 (50-150 sccm, ICP power 1500-2000 W) for 5-10 seconds. This process was repeated 100-300 times. The substrate was cooled to -10 to 10°C, and the etching rate was approximately 3-6 μm / min. The etching of the top layer of P-type silicon reached a maximum thickness of 1 μm before termination. Finally, the wafer was ashed using oxygen plasma (O2 flow rate 100-200 sccm, power 200-300 W, time 10-20 seconds). By removing residual photoresist (min), a silicon-based metasurface structure with vertical sidewalls (sidewall angle > 88°), an aspect ratio of over 10:1, and a feature size error of less than 50 nm can be fabricated. By adjusting the gas flow rate ratio, chamber pressure, and RF power, the anisotropy of the etching is controlled, and a silicon nanopillar array with good perpendicularity is etched onto the silicon surface. The etching depth is controlled to be 500 nm-1 μm, the nanopillar diameter is approximately 500 nm, and the period is approximately 500 nm. Ion implantation is used to etch B-type photoresist onto the sidewalls of the silicon pillars.+ Doping (ion implantation angle less than 10°), doping concentration range of 1.5 × 10⁻⁶ 12 ion / cm 3 ~3.5×10 15 ion / cm 3 After ion implantation, residual photoresist is removed by oxygen plasma ashing to obtain a clean silicon columnar metasurface structure.

[0035] Reference Appendix Figure 5 The substrate, after resist removal in step 3, is placed in the AVP-IBE etching system for a second maskless three-stage large-angle dynamic rotating ion beam etching (Angled-IBE). During the etching process, the etching gas is Ar, the etching protective gas is N2, and the vacuum inside the etching process chamber is 3.2 × 10⁻⁶. 7 Torr.

[0036] First stage: The sample stage rotates at a speed of 15° / s, the ion beam incident angle is set to a relatively steep 15°~25°, and high-speed longitudinal cutting is performed under a high electric field (accelerating voltage 550 V) for 90s. Second stage: The sample stage rotation speed is 25° / s, the ion beam incident angle is adjusted to 55°~65°, and the accelerating voltage is reduced to 300 V. Transverse tangential shear force is used to accelerate the etching of the silicon pillar sidewalls; The third stage: the sample stage rotates at a speed of 10° / s, the tilt angle is adjusted to a very gentle 75° angle, a weak beam of 150 V is applied for scanning for 20 s to eliminate the step stress caused by over-etching, and the surface of the frustum sidewall is flattened with low energy. After etching, a frustum-shaped silicon-based metasurface array structure was obtained, as shown in the attached figure. Figure 5 .

[0037] Step 4: Preparation of Si-QDs modified layered Ti3C2MXene composite material S1. Preparation of layered Ti3C2MXene composite material: 2.0 g of ground and sieved Ti3C2Al MAX phase powder was added to a polytetrafluoroethylene (PTFE) lined reactor. Under stirring conditions of 200 rpm to 800 rpm, 40 mL of a 30%–50% (w / w) hydrofluoric acid (HF) solution was slowly added, and the reaction was carried out at 20°C to 30°C for 12 h to 48 h. After the reaction, the supernatant was discarded by centrifugation (8000 rpm to 12000 rpm), and the black precipitate was repeatedly washed with ultrapure water until the pH of the washing solution was 6.5–7.0. Finally, the mixture was vacuum dried at 40°C to 60°C to obtain accordion-shaped multilayered Ti3C2MXene. The microstructure of the material is as follows: Figure 6As shown in (b).

[0038] Preparation of S2.Si-QDs: Under stirring at room temperature, 15 mg of DAPH was added to 5.0 mL of deionized water and stirred until fully dissolved. Then, 1.0 mL of DAMO was added dropwise to the solution. The reaction system was allowed to react at room temperature for 3 h. The product was first filtered through a 0.1 μm to 0.22 μm filter membrane, and then dialyzed in deionized water for 2 h to 8 h using a dialysis bag with a molecular weight cutoff of 500 Da to 3000 Da to obtain a purified aminated silicon quantum dot solution. The solution was collected and stored at 4 °C for later use. The microstructure of the material is shown in the attached figure. Figure 6 As shown in (c), the Fourier transform infrared spectra of Si-QDs are shown in Appendix. Figure 7 (a).

[0039] S3. Preparation of layered Ti3C2 MXene@Si-QDs composite material: 50 mg of the layered Ti3C2MXene material obtained in step S1 was ultrasonically dispersed in an ethanol / water mixed solvent (volume ratio 1:9 ~ 2:8) with an ultrasonic power of 100 W ~ 300 W and an ultrasonic time of 10 min ~ 30 min; under stirring at 200 rpm ~ 600 rpm, 25 mg of the aminated silicon quantum dot solution obtained in step S2 was added dropwise to the above dispersion, controlling the mass ratio of the layered Ti3C2 MXene material to the silicon quantum dots to be 10:1 ~ 2:1; the reaction was continued to be stirred at 20°C ~ 30°C for 12 h ~ 48 h; after the reaction was completed, the black precipitate was collected by centrifugation, washed repeatedly 3 ~ 5 times with an ethanol / water mixed solvent (volume ratio 1:1), and finally dried under vacuum at 40°C ~ 60°C to obtain the silicon quantum dot modified layered Ti3C2MXene composite material. The microstructure of the material is shown in the attached figure. Figure 6 As shown in (d), the Fourier transform infrared spectra of Ti3C2MXene and Ti3C2MXene@Si-QDs materials are attached. Figure 7 (b).

[0040] Step 5: The Ti3C2 MXene@Si-QDs composite material synthesized in Step 4 was dispersed in dimethyl sulfoxide and uniformly coated onto the Si-based metasurface structure prepared in Step 3 by spin coating. By controlling the spin coating speed and solution concentration, the composite material was partially embedded in the gaps between the Si nano-prisms or conformally covered on the surface of the nano-prism array, forming a closely contacted light-absorbing composite layer. It was then dried in a vacuum drying oven at 60°C for 2 hours.

[0041] Step 6: Electrode preparation On the surface of the shaped composite photoelectric conversion layer, a 6 mg / mL AgNWs solution was spin-coated onto the substrate surface to form a mesh-like high-transmittance detector signal acquisition anode. The Ag nanowires in the Ag-NWs solution have a diameter of no more than 30 nm. The microstructure of the light spot detector after the transparent anode is prepared is shown in the attached figure. Figure 8 As shown.

[0042] See appendix Figure 8 and attached Figure 9 After the transparent signal acquisition anode is prepared, the cathode contact area of ​​the photodetector is defined by a second photolithography process. The specific photolithography process and parameters are the same as in step 2. The substrate is then placed in the AVP-IBE etching system and etched down to the Si level. n- A layer was formed to create the cathode contact area. During etching, the sample stage rotated at a speed of 25° / s, the ion beam incident angle was 90°, the etching electric field acceleration voltage was 500V, and the etching time was 500s. After etching, the photoresist mask layer was removed using NVP resist remover.

[0043] See appendix Figure 10 The cathode and anode overlap area of ​​the photodetector was defined using a third photolithography process. Then, using an electron beam evaporation apparatus, Ti (as an adhesion layer) with a thickness of 20 nm and Au (as a conductive layer) with a thickness of 100 nm were deposited sequentially. After the evaporation was completed, a lift-off process was performed to form the Ti / Au electrode metal layer.

[0044] Through the above steps, a high-performance photodetector based on a silicon-based metasurface and a Si-QDs-modified Ti3C2MXene composite material is obtained. See the attached diagram for a schematic. Figure 11 .

[0045] Detection results of the photodetector prepared in the example: The photodetector prepared in this embodiment was subjected to photoelectric performance testing. Under laser irradiation at a wavelength of 635 nm, compared with the photodetector device with Si metasurface structure and the Si metasurface structure / Ti3C2MXene@Si-QDs detector, the Si metasurface structure / Ti3C2MXene@Si-QDs photodetector of this invention exhibits low light reflection in the light wavelength range of 400 nm-1050 nm (see Appendix). Figure 13Furthermore, the antireflection effect is more significant for light with wavelengths greater than 820 nm. In addition, the composite material of this invention exhibits significant photocurrent responses in both the visible (635 nm) and near-infrared (980 nm) bands. Particularly for the near-infrared band (980 nm), the photocurrent response generated by the pure Si metasurface structure is approximately 14.1 µA, while the composite structure of this invention shows a significant enhancement in photocurrent at this band (approximately 16.7 µA). This indicates that by introducing the Ti3C2MXene@Si-QDs heterojunction, the response range of the silicon-based detector has been successfully extended to the near-infrared region, and the response sensitivity far exceeds that of a single Si metasurface structure (see Appendix). Figure 13 and Figure 14 The transient response test results show that the accordion-like layered structure of the multilayer Ti3C2 MXene material provides an efficient two-dimensional electron transport channel. At the same time, the introduction of Si-QDs forms an 0D / 2D close heterojunction, which greatly promotes the separation and rapid transfer of photogenerated electron-hole pairs and effectively suppresses carrier recombination, thereby achieving a significant photoconductivity gain.

[0046] The Si metasurface structure / Ti3C2 MXene@Si-QDs photodetector prepared in this embodiment exhibits a fast and reversible current response to incident light in single-point scanning imaging tests, with a photocurrent reaching 5.7 × 10⁻⁶ A. Furthermore, its response time (rise / fall) is superior to that of similar MXene-quantum dot composite devices. These results demonstrate that the 0D / 2D heterojunction constructed by room-temperature chemical self-assembly in this invention can effectively enhance light absorption and accelerate carrier separation and transport, making it suitable for high-sensitivity, high-stability photodetection and imaging applications.

Claims

1. A photodetector based on a metasurface structure and MXene composite material, characterized in that, The photodetector comprises a multilayer Ti3C2MXene@Si-QDs composite material. The photoelectric conversion region of the photodetector is composed of a silicon-based metasurface structure and a layered Ti3C2MXene@Si-QDs composite material. The metasurface structure is a frustum-shaped subunit array formed by Si-based semiconductor material. The multilayer Ti3C2MXene@Si-QDs composite material covers the surface of the silicon-based metasurface structure. The multilayer Ti3C2 MXene@Si-QDs composite material includes multilayer Ti3C2 MXene material and Si-QDs loaded on the surface and / or between the layers of the multilayer Ti3C2 MXene material; the surface of the Si-QDs contains amino functional groups, and the Si-QDs are tightly anchored to the Ti-O-Si bonds through hydrogen bonding and / or chemical bonding between the amino functional groups and the oxygen-containing groups -O, -OH and / or fluorine-containing groups -F at the end of the surface of the multilayer Ti3C2 MXene material, forming a stable interfacial contact.

2. The photodetector based on metasurface structure and MXene composite material according to claim 1, characterized in that, The spacing between adjacent frustum subunits of the metasurface structure is 500 nm to 1 μm.

3. The photodetector based on metasurface structure and MXene composite material according to claim 1, characterized in that, The multilayer Ti3C2MXene has an accordion-like layered structure.

4. The photodetector based on metasurface structure and MXene composite material according to claim 1, characterized in that, The particle size of the Si-QDs is 2 to 10 nm, and the particle size distribution deviation does not exceed ±1.5 nm; the mass ratio of the Si-QDs to the multilayer Ti3C2MXene material is 1:(1 to 10).

5. The photodetector based on metasurface structure and MXene composite material according to claim 1, characterized in that, The preparation method of the layered Ti3C2MXene@Si-QDs composite material includes the following steps: (1) Preparation of layered Ti3C2MXene material: The ground and sieved Ti3C2Al MAX phase powder was slowly added to a hydrofluoric acid solution with a mass fraction of 30%~50% under stirring conditions, and reacted at 20°C~30°C for 12 h~48 h; after the reaction, the supernatant was discarded by centrifugation, and the black precipitate was repeatedly washed with ultrapure water until the pH of the washing solution was 6.5~7.

0. Finally, it was vacuum dried at 40°C~60°C to obtain accordion-shaped multilayer Ti3C2 MXene material; (2) Preparation of Si-QDs dispersion; (3) The multilayer Ti3C2MXene material obtained in step (1) is ultrasonically dispersed in an ethanol / water mixed solvent; under stirring conditions, the aminated Si-QDs solution obtained in step (2) is added dropwise to the above dispersion; the reaction is continued to be stirred at 20°C ~ 30°C for 12 h ~ 48 h; after the reaction is completed, the black precipitate is collected by centrifugation, washed repeatedly with an ethanol / water mixed solvent, and finally dried under vacuum at 40°C ~ 60°C to obtain the layered Ti3C2MXene@Si-QDs composite material.

6. A method for fabricating a photodetector based on a metasurface structure and MXene composite material as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: Step 1: Provide a heavily doped silicon substrate; Step 2: Define the planar pattern of the silicon metasurface structure on the surface of the silicon substrate using a photolithography process; Step 3: Based on the planar pattern, a three-dimensional silicon metasurface structure is formed on the surface of the silicon substrate using deep reactive ion beam and dynamic rotating ion beam etching processes; Step 4: Prepare layered Ti3C2 MXene@Si-QDs composite material; Step 5: The layered Ti3C2 MXene@Si-QDs composite material is bonded to the surface of the silicon-based metasurface structure to form a photoelectric conversion composite layer; Step 6: Prepare a transparent signal acquisition anode electrode on the photoelectric conversion composite layer, and prepare a metal thin film signal acquisition cathode electrode on both sides of the photoelectric conversion composite layer to obtain a photodetector.

7. The method for fabricating a photodetector based on a metasurface structure and MXene composite material according to claim 6, characterized in that, The three-dimensional silicon metasurface structure formed in step 3 is first formed into pillars with a diameter of 500nm-1μm and a height of 100nm-1μm by deep reactive ion beam etching (DRIE) process; then, the sidewalls of the pillar structure are etched at different rates by multi-stage large-angle dynamic rotating ion beam etching (Angled-IBE) technology to form a frustum-shaped subunit array.

8. The method for fabricating a photodetector based on a metasurface structure and MXene composite material according to claim 6, characterized in that, The anode electrode prepared in step 6 is a transparent mesh structure Ag nanowire, which is reliably overlapped with the metal thin film on both sides of the light absorption composite layer; the cathode electrode for signal acquisition is a ring structure or strip structure metal thin film outside the anode overlap area.

Citation Information

Patent Citations

  • Application of 3-(2-aminoethylamino)propyltrimethoxysilane to prepare ultra-bright fluorescent silicon quantum dots

    CN104003392A

  • Application of diethylenetriamine propyl trimethoxy silane in preparing water-soluble silicon quantum dot

    CN104016348A